Digital humanities and educational ecosystem: towards a new epistemic structure from digital didactics - González-Gutiérrez, Sara; Merchán-Sánchez-Jara, Javier (Anuario ThinkEPI, 2022)
This paper critically addresses the conditioning factors and considerations underlying the projection of Digital Humanities, as an operational discipline, to the field of educational praxis. The colonisation of this new area of competence consolidates the trend of translation of Digital Humanities, from its consideration as a methodological apparatus at the service of research, to the environment of professional praxis in various areas of knowledge. In order to address this issue, a conceptual delimitation is layed out to characterise the Digital Humanities in the academic environment, as opposed to the common use of the concept of ICT in Education. From this perspective, the development of new epistemic cultures is addressed in terms of the new ways of thinking implied by the flows and channels of knowledge reception in digital educational environments, as well as the need to integrate the Digital Humanities into these ecosystems in order to design and implement tools and sources of information semantically adapted to the needs of the environment, in relation to the different curricular requirements or pedagogical perspectives of each academic context. Finally, a brief allusion is made to how all these issues come together in what is known as "digital didactics", understood as the set of strategies that inspire the new teaching-learning processes, optimising the pedagogical possibilities offered by new technological developments.